2011
DOI: 10.1253/circj.cj-10-0490
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Sensing Ion Channel 3, But Not Capsaicin Receptor TRPV1, Plays a Protective Role in Isoproterenol-Induced Myocardial Ischemia in Mice

Abstract: Background: Cardiac angina is the hallmark of myocardial ischemia, but the role of the cardiac sensory nerve has received relatively little attention. Recently, both acid-sensing ion channel 3 (ASIC3) and capsaicin receptor (TRPV1) have been suggested as important mediators in sensing myocardial ischemia. However, studies comparing the physiological roles of ASIC3 and TRPV1 in the neuronal - cardiac sensing circuits in vivo are lacking. Methods and Results:Isoproterenol (1.5 mg/kg, intraperitoneally) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It can be activated by low extracellular pH to evoke both transient and sustained inward currents, which can be further enhanced by lactate [ 1 2 3 4 5 6 ]. ASIC3 has been associated with myocardial ischemic pain, muscle pressor reflex, and possible imbalanced autonomic regulation [ 7 8 9 10 ]. The ASIC3 gene, located on chromosome 7q35-36.1, has three transcript variants encoding distinct isoforms generated by alternative splicing [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be activated by low extracellular pH to evoke both transient and sustained inward currents, which can be further enhanced by lactate [ 1 2 3 4 5 6 ]. ASIC3 has been associated with myocardial ischemic pain, muscle pressor reflex, and possible imbalanced autonomic regulation [ 7 8 9 10 ]. The ASIC3 gene, located on chromosome 7q35-36.1, has three transcript variants encoding distinct isoforms generated by alternative splicing [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physiological significance of ASIC3 is emphasized by sensory neurons expressing ASIC3 or ASIC3-like currents innervating skin, heart, muscle, vessels, and many visceral tissues [512]. Because of its specific expression in sensory neurons and its property of proton-evoked sustained current, ASIC3 has attracted much attention in pain studies [1315]. …”
Section: Introductionmentioning
confidence: 99%
“…[34,35]. Cheng et al indicated that acid-sensing ion channel 3, but not capsaicin receptor TRPV1, played a protective role in isoproterenol-induced myocardial ischemia in mice [36].…”
Section: Discussionmentioning
confidence: 99%